"Hidden gains"? Measuring the impact of mindfulness-based interventions for people with mild traumatic brain injury: a scoping review. (29th July 2022) - Lovette, Brenda C.; Kanaya, Millan R.; Bannon, Sarah M.; Vranceanu, Ana-Maria; Greenberg, Jonathan
ABSTRACT: Background: Mindfulness-based interventions can support recovery from mild traumatic brain injury (mTBI). Although measurement is a key determinant of outcomes, there is no comprehensive assessment of measurement approaches used to capture outcomes of these programs. Here, we review the domains targeted, measurement techniques used, and domains and techniques most affected by mindfulness-based interventions for mTBI. Methods: We conducted a scoping review. After screening and full-text review, we included 29 articles and extracted data related to measurement domains, techniques, and results. Results: We identified 8 outcome domains, each with multiple subdomains. The most common domains were cognitive symptoms and general health/quality of life. No quantitative studies directly assessed sleep, physical-function, or pain-catastrophizing. Self-report was the most common measurement technique, followed by performance-based methods. Coping, somatic symptoms, emotional symptoms, stress response, and domains of cognition (particularly attention) were the most frequently improved domains. Qualitative results described benefits across all domains and suggested novel areas of benefit. Biomarkers did not reflect significant change. Conclusions: Mindfulness-based interventions for mTBI impact a range of clinical domains and are best captured with a combination of measurement approaches. Using qualitative methods and expanding the breadth of outcomes may help capture underexplored effects of mindfulness-based interventions for mTBI.